SISTEM INFORMASI AKUNTASI (SAKTIPOL) UNTUK PENGELOLAAN KEUANGAN PRODUK BATIK DAN BORDIR DI DESA PAKISAJI KABUPATEN MALANG - Mungki Astiningrum; Yuri Ariyanto; Dwi Puspitasari; Atiqah Nurul Asri; Moch Zawaruddin A (P3M Politeknik Negeri Malang, 2020)
The increasingly heavier life demands, especially in the economic sector, have encouragedhousewives in Desa Pakisaji, Kabupaten Malang to set up Ron Tuwuh batik tulis business groupand Prohandji Embroidery business group. The batik works are quite good and have begun to bewell-known, especially among government agencies in Kabupaten Malang, as well as theirembroidery works. There have been several steps taken to develop themselves in terms of design,namely by establishing a partnership with the 2019 Partnership PKM team of InformationTechnology Department of State Polytechnic of Malang. They have learned to design usingapplications built and as a result their designs become more up-to-date and the workmanshipbecomes more efficient. In an effort to sustain this program, this year the same team also continuedPKM Partnership by solving other problems faced. From the results of interviews and observationsconducted, it was found that each group had problems in the field of financial recording. Theincome of the batik cloth and the embroidered cloth are still recorded manually so that the financialrecording process of both income and expenditure is ineffective and inefficient. From theseproblems, an Accounting Information System, SAKTIPOL was created which aims to assist bothgroups in the field of financial management. In addition, after the system was designed, this teamthen provided training and assistance in the use of this computer and internet-based application